1987
DOI: 10.1021/bi00378a008
|View full text |Cite
|
Sign up to set email alerts
|

The majority of cellular fatty acid acylated proteins are localized to the cytoplasmic surface of the plasma membrane

Abstract: The BC3Hl muscle cell line was previously reported to contain a broad array of fatty acid acylated proteins [Olson, E. N., Towler, D. A., & Glaser, L. (1985) J. Biol. Chem. 260, 3784-3790]. Palmitate was shown to be attached to membrane proteins posttranslationally through thiol ester linkages, whereas myristate was attached cotranslationally, or within seconds thereafter, to soluble and membrane-bound proteins through amide linkages [Olson, E. N., & Spizz, G. (1986) J. Biol. Chem. 261, 2458-2466]. The tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…GLUT1 has six cysteine residues, several of which are predicted to have access to the cytoplasmic compartment (33). This localization favors palmitoylation (60). Indeed, Pouliot and Beliveau (38) have demonstrated that GLUT1 in brain capillaries is palmitoylated.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 has six cysteine residues, several of which are predicted to have access to the cytoplasmic compartment (33). This localization favors palmitoylation (60). Indeed, Pouliot and Beliveau (38) have demonstrated that GLUT1 in brain capillaries is palmitoylated.…”
Section: Discussionmentioning
confidence: 99%
“…First, the native structure of FABP may possess a more appropriate conformational state for easy binding to its putative receptor. It has been shown that platelet-derived CD36 is part of the signal-transduction system associated with c-src oncogene family kinases [15] that play a role in the control of cell growth [27]. It is interesting to note that recently Yang et al [33] demonstrated that recombinant, rat intestine FABP and bovine liver type FABP, did not inhibit the growth of mouse epithelial cells, as did mammary-derived growth inhibitor (MDGI) FABP or bovine heart FABP.…”
Section: Detection Of Fabp-cd36 Complexes By Immunoprecipitation and mentioning
confidence: 99%
“…Golgi and plasma membranes were isolated by sucrose gradient centrifugation (33), and the identity and purity of these membrane populations were determined by enzyme markers. Alkaline phosphatase and P-1,3-galactosyltransferase have been reported to be plasma membrane and Golgi membrane markers, respectively, consistent with results of this study.…”
Section: Figmentioning
confidence: 99%